A participação para o desenvolvimento: um estudo sobre a construção de significados a partir de seu fenômeno temporal - Calgaro Neto, Silvio (2015)
Since the second half of the twentieth century there was been the emergence and the introduction of participatory discourses at the socio-institutional organizations dedicated to development, however a particular way to manipulate this discourse was resulted, different stricto sensu to the references and meanings related to the participatory discourse and ideals. Under the practical possibility to socially applicate the radical participatory models, has been a dissemination of theoretical and practical experiences that aplificate the sense of participatory discourse. It has been considered a potential element to renovate the democratic structures, that claims for a relativization to the technical and centralist models of institutional decisions. This new and particular way to operationalize the participatory processes changed the polar position between participation and representation. That was historically opposed, reached the possibility to operate together, transforming and amplifying their references and meanings. To this way that we call lato sensu model of participation we can find a large numbers of methodological, typological and index approaches and tools attempting to reach yours discursive, dialogical and practical utilization. In this context, a conceptual actualization was required and the political theorists asked to understand this particular and new way to use the participatory discourse, that, apparently, do not content the strict references and meanings. A inter-discursive process has been occurred and distinctive relations ask to attention at the moment to explore a new participatory phenomena, trying to brings up answers about this that we also call participation. Therefore, this thesis is dedicated to unveiling this phenomenon that from the words of it critical authors reproduces helpful meanings to attempt the institutional requirements, but with a soft inclination to discuss about the direct intervention of the people in the construction of institutional structures and social changes. So, in addition to treating the theoretical problems that emerges from the lato sensu participatory experiences, this thesis had been oriented to investigate the possibles meanings assigned from these, bringing to this document meaning expressions of those people from own participatory experience. We had been adopted the methodological basis of phenomenology, that presupposes that people expressions can be used like objective subsidies to reach meaning references and relations around the phenomena. Conducing the unveiling method of perfect circularity, this thesis was composed by four principals sections, where had been inserted the chapters. These sections seek to show, respectively, the theoretical, methodological, phenomenological and critical relations that build this thesis, orienting to specify the particular models of participation investigated in this empirical work, that occurred on the structures of International Development Cooperation, from where emerges the particular model of participation for development. With the effort to contribute on the construction of meanings about the participation and introduce elements to understand what is this that we also call participation, this thesis concludes with a new perspective about the initials issues, whereupon the people expressions indicates the necessity of participatory critical look to the personal possibilities, more than institutional possibilities.